The Moderating Effects of Sex on Consequences of Childhood Maltreatment: From Clinical Studies to Animal Models - White, Jordon D.; Kaffman, Arie (Frontiers in Neuroscience, 2019)
Stress has pronounced effects on the brain, and thus behavioral outputs. This is particularly true when the stress occurs during vulnerable points in development. A review of the clinical literature regarding the moderating effects of sex on psychopathology in individuals exposed to childhood maltreatment (CM) is complicated by a host of variables that are difficult to quantify and control in clinical settings. As a result, the precise role of sex in moderating the consequences of CM remains elusive. In this review, we explore the rationale for studying this important question and their implications for treatment. We examine this issue using the threat/deprivation conceptual framework and highlight a growing body of work demonstrating important sex differences in human studies and in animal models of early life stress (ELS). The challenges and obstacles for effectively studying this question are reviewed and are followed by recommendations on how to move forward at the clinical and preclinical settings. We hope that this review will help inspire additional studies on this important topic.